2011
DOI: 10.1158/1055-9965.epi-10-1187
|View full text |Cite
|
Sign up to set email alerts
|

Risks for Persistence and Progression by Human Papillomavirus Type 16 Variant Lineages Among a Population-Based Sample of Danish Women

Abstract: Background: Little is known about factors determining HPV16 persistence and progression, but several studies have suggested that genetic variants may play a role.Methods: HPV16-positive women with normal cytology in a large Danish cohort were reassessed for HPV16 status at 2 years and followed-up for cervical intraepithelial neoplasia 3 or worse (CIN3þ) over 11 years through linkage with a national pathology database. Relative risks for clearance, persistence, and progression were compared with different HPV16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 39 publications
1
67
1
1
Order By: Relevance
“…However, these SNPs did not show evidence of defining phylogenetic subgroups. Thus, epidemiological studies should compare these non-lineage-specific SNPs within a given lineage only, following the example of studies that have suggested that the EUR-350G and EUR-350T sublineages differ in their risks for viral persistence (9) and/or cervical cancer (9,10,22,28). However, this approach is unlikely to be statistically feasible for rarer SNPs, and care should also be taken not to overinterpret their importance (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these SNPs did not show evidence of defining phylogenetic subgroups. Thus, epidemiological studies should compare these non-lineage-specific SNPs within a given lineage only, following the example of studies that have suggested that the EUR-350G and EUR-350T sublineages differ in their risks for viral persistence (9) and/or cervical cancer (9,10,22,28). However, this approach is unlikely to be statistically feasible for rarer SNPs, and care should also be taken not to overinterpret their importance (13).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, based principally on the sequencing of E6 and/or the LCR in studies from Europe and the Americas, have suggested that HPV16 variants can influence viral persistence and the development of cervical cancer (9,24,25,28,30). However, for future large-scale epidemiological studies, it is important to have a complete and standardized classification of HPV16 variant sublineages worldwide.…”
mentioning
confidence: 99%
“…While most HPV infections are asymptomatic and eventually cleared by the immune system, in some cases the infection will persist and, in rare cases, lead to cancer (reviewed in reference 2). Evidence suggests that not only HPV type but also sequence variations within high-risk HPVs may influence viral persistence and clinical outcome (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…According to geographic location and ethnic group, HPV16 variants have been classified into 4 lineages; 1) European-Asian (EAs) including the sublineage European (E, the prototype of HPV16) and Asian (As), 2) African 1 (AFR1), 3) African 2 (AFR2) and 4) North American/ Asian-American (NA/AA) including the sublineage North American, Asian-American 1 and Asian-American 2 (Yamada et al, 1997;Cornet et al, 2012). Epidemiological studies show an association between cervical cancer and HPV16 variants and report that HPV16 E6 variants may be more oncogenic than the prototype and thus carry a higher risk for development of invasive cervical disease (Xi et al, 2007;Schiffman et al, 2010;Gheit et al, 2011;Mosmann et al, 2015). Many studies have shown high prevalence of the HPV16 Asian variant or HPV16As (member of EA lineages) in invasive cervical cancer and an association with cervical cancer progression in Asian populations (Kang et al, 2005;Choi et al, 2007;Chopjitt et al, 2009;Chang et al, 2013;Pientong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%